Уточнення типового сценарію за додатковими показниками - Kuzminykh, Valeriy; Koval, Oleksandr; Otrokh, Sergiy (Kamianets-Podilskyi National Ivan Ohiienko University, 2019)
The problems in the quality assessment modeling scenarios collecting information flow on an extensive network of the example of the problem of building and further optimization scenarios to analyze the budget process on an extensive network. Shown use structured approach to the ontology as considered most appropriate to the task of presenting the structure as a graph. Moved assessment of the effect of the use of partial information previously obtained by constructing scenarios collecting information flow on the network, described the count, with further refinement information. An formalized description of the hierarchical structure of the system. An example of the structure of the interaction of ontology elements for the problem of budget analysis is presented.The use of an integrated approach based on finding the shortest path in the graph and model ontology as a graph that realizes the possibility of using algorithms based on traversing vertices in layers of hierarchy.An approach to building breadth-first search algorithm that significantly reduces the time to find ways of building scenarios collect information on streaming extensive network. Described in the article approach to building quality assessment algorithm simulation scenarios collect information on flow tested an extensive network in the development of pilot systems, financial analysis of regional budgets. The algorithm allows to develop a set of software tools that provides plenty full and holistic problem solving refinement and optimization scenarios searching and collecting information flow on an extensive network. One of the promising areas of application of this approach to assessing the quality of the simulation scenarios are used to build its capacity information and analytical systems. This will significantly reduce the time and improve the quality of finding the necessary flow of information.